2012
DOI: 10.3917/spub.122.0121
|View full text |Cite
|
Sign up to set email alerts
|

Épidémie de rougeole et de sa riposte en 2009, dans la région de Dakar, Sénégal

Abstract: In 2009, the region of Dakar (Senegal) experienced a major measles epidemic, in the context of the failure of the immunization program. The objective of this study was to examine the epidemic and the effectiveness of the response. A cross-sectional epidemiological study of all cases of measles confirmed by laboratory tests or epidemiological linkage was conducted between June and December 2009. The study also assessed the effectiveness of the response. The results show that out of 767 confirmed cases, less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
2
8
0
3
Order By: Relevance
“…The most affected age groups were children aged 1 to 5 (44.44%). Similar observations were observed in other African countries where the most affected groups were the 1 to 4 years old (36.87%) in Niger [ 6 ], in Mali the 0 to 5 years (24%) [ 10 ], in Ethiopia 1 to 4 years (31.3%) [ 11 ], children under 5 (67.4%) in Senegal [ 12 ], and children aged 9 months to 5 years in Uganda [ 13 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The most affected age groups were children aged 1 to 5 (44.44%). Similar observations were observed in other African countries where the most affected groups were the 1 to 4 years old (36.87%) in Niger [ 6 ], in Mali the 0 to 5 years (24%) [ 10 ], in Ethiopia 1 to 4 years (31.3%) [ 11 ], children under 5 (67.4%) in Senegal [ 12 ], and children aged 9 months to 5 years in Uganda [ 13 ].…”
Section: Discussionsupporting
confidence: 83%
“…In our sample, 71.4% of the subjects were not vaccinated, these results are lower than those noted in studies by Seck et al . 88.5% [ 12 ], Alkassoum et al . 93.1% [ 6 ], and Palarama et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm previous studies in sub-Saharan Africa which shows considerable delays in administration of measles administration after 12 months [ 11 , 24 ]. In 2009, a massive outbreak occurred in Senegal with continuous virus transmission from late 2009 to early 2010 [ 16 , 31 ]. During this outbreak, it was confirmed that 11,3% of affected children did receive a measles contained vaccine but was not correctly immunized.…”
Section: Discussionmentioning
confidence: 99%
“…Since measles is highly endemic and frequently affects infants in Senegal, routine measles vaccination is recommended at the 9th month of age with a second dose at 15th month. Additionally, a dose of yellow fever is also given at the age of nine months [9,10]. Regardless of successes, vaccine-preventable diseases are the leading cause of childhood mortality in Senegal while the under-five child mortality rate is still high as 45 per 1000 live births [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported their findings on child immunization coverage but few of them generated evidence about the socio-demographic factors associated with full immunization among children. However, the existing studies focused on either specific target areas (e.g., urban, rural, geographic location), among younger aged children or on certain vaccine-preventable diseases [10,15,16]. Also existing studies are unable to present the current scenario of full immunization coverage as these studies often used either previous round data or not representative of the country scenario of full immunization status.…”
Section: Introductionmentioning
confidence: 99%